Efektivitas Edmodo Berbasis Inqury Based Learning Terhadap Peningkatan Hasil Belajar Siswa Kelas XI IPS 1 SMA Ma’arif Nu Jatinegara - Muhammad Yusuf Zamzami; Adi Sucipto; Mutiara Nabila Aprinthasari (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
Abstract This study aims to determine whether there is an improvement in learning outcomes—comparing results before and after using Edmodo-among Grade XI Social Studies (IPS) students at SMA Ma’arif NU Jatinegara. The study sample consisted of 34 students selected via purposive sampling. Data collection methods included testing, documentation, and observation, while data analysis employed descriptive percentage statistics and t-tests. The results showed an average pre-test score of 60.41 and an average post-test score of 78.29. Furthermore, a difference was observed in the learning outcomes regarding the topic of